STUDENTS' ATTITUDES TOWARDS HOME ECONOMICS IN THE COLLEGES OF EDUCATION: THE ROLE OF INSTRUCTOR’S DIDACTIC SKILLS - Rogers Beatrice , Ossia (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Home economics is an essential subject in Nigeria's educational system, intending to enable students to develop a positive relationship with skills and a healthy living pattern by acquiring various do-it-yourself skills. An increasing body of evidence lends credence to the claim that the field has been struggling with low enrollment rates over the years. Thus, the present study examined the instructor’s didactic skills as a factor influencing the student’s attitude toward home economics education. Ninety-six undergraduates enrolled in the home economics department from two higher education institutions in the Enugu State of Nigeria participated in the study. A simple percentage score indicates that most students (65.5%) indicated a positive attitude towards home economics education, while less (34.5%) showed negative attitudes. Furthermore, a simple regression analysis was performed to test the study hypothesis. The result revealed that the instructor’s didactic skills positively predicted students’ attitudes toward home economics education. The result has implications for the development of home economics in the colleges of education in Nigeria.